Introduction to tyre technology : Part I. Bias or crossply tyre. Part II.Radial tyre (BOOK LOST, COST RECOVERED) - CHAKRAVARTY, S N (Polym Consultants New Delhi, 2012)
Book lost and cost recovered from Sri. Madhusoodanan, Principal Scientist, Rubber technology (Receipt No10470 dated 19.10.2023 for Rs 810.00
Book lost and cost recovered from Sri. Madhusoodanan, Principal Scientist, Rubber technology (Receipt No10470 dated 19.10.2023 for Rs 810.00
Book lost and cost recovered from Sri. Madhusoodanan, Principal Scientist, Rubber technology (Receipt No10470 dated 19.10.2023 for Rs 810.00
Keywords: Crossply tyre; Radial tyre; Tyre technology